Legal Analysis of the Responsibility of Expedition Companies X to Service Users Goods that are Damaged or Lost During Stacking in the Stacking Field - Richa Yohana Rusli Siahaan; Martono Anggusti; Jinner Sidauruk (Dinasti Research, 2025)
Sea transportation plays a very important role in international trade as one of the main components in the process of distributing goods. Nonetheless, the losses incurred in sea transportation activities are often greater than the losses caused by the transportation process itself, such as damage, shortages, and loss of goods that can occur during the process of unloading goods at the port by freight forwarding companies by sea. This study aims to analyze the limits of obligations and legal relationships between freight forwarding companies, carriers, and sea freight forwarding companies in the context of sea transportation activities. Using a normative legal research methodology, this study utilizes legal resources that include relevant laws and regulations as well as applicable court decisions, with a legislative approach and a case approach. The results of this study show that, first, the limitation on the responsibility of the expedition company regulated in Article 87 of the Commercial Code (KUHD), as well as the limitation of the carrier's liability regulated in Article 40 and Article 41 of Law Number 17 of 2008 concerning Shipping, unlawful acts under Article 1365 of the Civil Code, and the responsibility of the sea transportation expedition company in terms of providing convenience, licensing, supervision, and the implementation of order in sea transportation activities, as stipulated in Cassation Decision Number 2665 K/Pdt/2022 which corroborates the decision of the Medan District Court in case Number 728/Pdt.G/2016/PN.Mdn, is in accordance with and includes legal objectives which include legal certainty, justice, and benefits for all parties involved.